Parasite infections in a social carnivore: Evidence of their fitness consequences and factors modulating infection load. Issue 15 (11th July 2019) - Ferreira, Susana Carolina Martins; Hofer, Heribert; Madeira de Carvalho, Luis; East, Marion L.
Abstract: There are substantial individual differences in parasite composition and infection load in wildlife populations. Few studies have investigated the factors shaping this heterogeneity in large wild mammals or the impact of parasite infections on Darwinian fitness, particularly in juveniles. A host's parasite composition and infection load can be shaped by factors that determine contact with infective parasite stages and those that determine the host's resistance to infection, such as abiotic and social environmental factors, and age. Host–parasite interactions and synergies between coinfecting parasites may also be important. We test predictions derived from these different processes to investigate factors shaping infection loads (fecal egg/oocyte load) of two energetically costly gastrointestinal parasites: the hookworm Ancylostoma and the intracellular Cystoisospora, in juvenile spotted hyenas ( Crocuta crocuta ) in the Serengeti National Park, in Tanzania. We also assess whether parasite infections curtail survival to adulthood and longevity. Ancylostoma and Cystoisospora infection loads declined as the number of adult clan members increased, a result consistent with an encounter‐reduction effect whereby adults reduced encounters between juveniles and infective larvae, but were not affected by the number of juveniles in a clan. Infection loads decreased with age, possibly because active immune responses to infection improved with age. Differences in parasite load between clans possibly indicate variation in abiotic environmental factors between clan den sites. The survival of juveniles (<365 days old) to adulthood decreased with Ancylostoma load, increased with age, and was modulated by maternal social status. High‐ranking individuals with low Ancylostoma loads had a higher survivorship during the first 4 years of life than high‐ranking individuals with high Ancylostoma loads. These findings suggest that high infection loads with energetically costly parasites such as hookworms during early life can have negative fitness consequences. Abstract : Individuals in wild mammal populations substantially differ in their gastrointestinal parasite composition and infection load. The Darwinian fitness consequences of intestinal parasites are rarely investigated. Using coprological examination of feces from known juvenile spotted hyenas in the Serengeti ecosystem, we identified a range of factors that influenced the infection loads of two energetically costly parasites (the hookworm Ancylostoma and the intracellular Cystoisospora ). As the number of adult clan members increased, Ancylostoma and Cystoisospora infection loads in juveniles decreased, suggesting an encounter‐reduction effect whereby adults reduced encounters between juveniles and infective hookworm larvae. High infection load of both these parasites increased the occurrence of other coinfecting parasites. Finally, juvenile survival to adulthood and longevity decreased with increasing Ancylostoma infection load, particularly in offspring of low‐ranking mothers.